Investment in transport infrastructure, regulation, and gas-gas competition (2010)
This paper develops a simple model in which a regulated (upstream) transporter provides capacity to a marketer competing in output with an incumbent in the (downstream) gas commodity market. The equilibrium outcome of the firms' interaction in the downstream market is explicitly taken into account by the regulator when setting the transport charge. We consider various forms of competition in this market and derive the corresponding optimal transport charge policies. We then run simulations that allow us to perform a comparative welfare analysis of these transport infrastructure investment policies based on different assumptions about the intensity of the competition that prevails in the gas commodity market. © 2009 Elsevier B.V.